1979
DOI: 10.1084/jem.149.5.1069
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of regulation of cell-mediated immunity. III. The characterization of azobenzenearsonate-specific suppressor T-cell-derived-suppressor factors.

Abstract: Delayed type hypersensitivity to the hapten azobenzenearsonate (ABA) can be induced and suppressed by the administration of hapten-coupled syngeneic spleen cells by the appropriate route. Suppressor T cells stimulated by the intravenous administration of ABA-coupled spleen cells have been shown to produce a discrete subcellular factor(s) which is capable of suppressing delayed type hypersensitivity to azobenzenearsonate in the mouse. Such suppressor factors may be produced by the mechanical disruption of suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…Takemori & Tada (1975) first demonstrated that the activity of afferent "Tsilike" suppressor cells could be mediated by the soluble protein fraction of suppressor cell lysates. Since these studies, soluble suppressor factors have been isolated in a number of systems (Yamauchi et al 1981, Kapp et al 1976, Waltenbaugh et al 1977) including the ABA system where sonicates, freeze-thaw extracts and supernatants from Tsi-containing splenocyte populations have been shown to suppress the DTH and CTL responses to ABA (Greene et al 1979a(Greene et al , 1982b. Effective suppression is only observed when the TsFi is administered beginning on or before the day of immunization, characterizing the factor, as was the cell from which it was derived, as a mediator of afferent suppressive activity.…”
Section: Previous Studies In the Aba Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Takemori & Tada (1975) first demonstrated that the activity of afferent "Tsilike" suppressor cells could be mediated by the soluble protein fraction of suppressor cell lysates. Since these studies, soluble suppressor factors have been isolated in a number of systems (Yamauchi et al 1981, Kapp et al 1976, Waltenbaugh et al 1977) including the ABA system where sonicates, freeze-thaw extracts and supernatants from Tsi-containing splenocyte populations have been shown to suppress the DTH and CTL responses to ABA (Greene et al 1979a(Greene et al , 1982b. Effective suppression is only observed when the TsFi is administered beginning on or before the day of immunization, characterizing the factor, as was the cell from which it was derived, as a mediator of afferent suppressive activity.…”
Section: Previous Studies In the Aba Systemmentioning
confidence: 99%
“…Characterization of TsFi has revealed that it is an antigen-binding molecule whose activity can be adsorbed on ABA-but not TNP-derivatized cells (Greene et al 1979a). When generated in mice with the Igh-1^ or Igh-l** genotype, the ABA-induced TsFi bears idiotopes recognized by rabbit anti-cross-reactive idiotypic antibody (Bach et al 1979).…”
Section: Previous Studies In the Aba Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In many cases these cells have been shown to release suppressor factors that block the appearance of antibody-forming cells (18,20,34,48). Also, haptens, either on proteins or on autologous cells, may induce specifi c T s F (14,54). Cellular immune re sponses to alloantigens or tumor antigens may be shown to be regulated by suppressor cells and T s F (15,38).…”
Section: Antigen-specific Suppressor Factorsmentioning
confidence: 99%